Dynamic scheduling algorithm for LTE uplink with smart‐metering traffic. Issue 10 (24th February 2017) - Amarasekara, Bhagya; Ranaweera, Chathurika; Evans, Rob; Nirmalathas, Ampalavanapillai
Abstract: Long‐term evolution (LTE) is a promising last mile access candidate technology for the smart‐metering communication architecture. However, when the mobile LTE network is used to support smart meters (SMs), the quality‐of‐service (QoS) requirements of the smart‐metering traffic as well as all the other typical mobile network traffic need to be ensured. This becomes problematic when the network users generate diverse traffic types that have different QoS requirements. Therefore, in this paper, we propose a dynamic bandwidth scheduling algorithm to ensure the required QoS of various traffic types arising from both SMs and mobile users. Our proposed dynamic bandwidth allocation algorithm integrates two schedulers that are designed for periodic and emergency SM traffic situations that have different SM traffic intensities and QoS requirements. Designing of two schedulers provides the advantages of leveraging the particular traffic characteristics of these two diverse operational situations and achieving the maximum use of resources to ensure QoS requirements. In addition, to alleviate potential problems created by simultaneous emergency SM traffic, we also propose a method that deploys a random delay for SM packet transmissions. We analyse the delay and packet drop ratio of diverse traffic types when both the LTE base station scheduler and the SMs deploy our proposed methods under either periodic or emergency SM traffic conditions in the smart grid. Our results show that our proposed mechanisms are capable of satisfying the QoS requirements of both mobile users and SMs under diverse traffic conditions. Abstract : In this paper, we investigate how mobile long‐term evolution network can support transmission of smart‐metering traffic while providing required quality‐of‐service level for all network users. We propose an uplink dynamic scheduler for long‐term evolution evolved NodeB that has 2 schedulers tailored for the periodic and emergency smart meter situations. Further, we propose delay allocation for emergency smart‐metering traffic transmission at smart meters. From our proposed solutions, we are able to achieve the required quality‐of‐service level for all users.